2022
DOI: 10.1002/ejlt.202100106
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Rates of Docosahexaenoic and Eicosapentaenoic Acids into Cow's Milk in Pasture Based and Feed‐Lot Management Systems

Abstract: The aim of the research is to assess the transfer of docosahexaenoic (DHA) and eicosapentaenoic (EPA) into cow's milk following supplementation with rumen protected fat supplements (rumen protected omega fat, RPOF). In pasture based and in feed‐lot management systems the transfer of DHA and EPA is 19–20% following supplementation with equal proportions of DHA and EPA (20–25 g/cow/day); the DHA and EPA level in milk are at 0.4% of the total fatty acids for each. There is no change in milk yield, protein, and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The findings of this investigation suggest that supplementation of UFA and/or PUFA sources can improve fatty acid profile and reduce the negative effects of biohydrogenation in the rumen. Another study conducted by Gulati et al [30] also found that a transfer of 19-20% of EPA and DHA into milk is achievable from feed management, whether they are raised on pasture or fed with a diet high in inert fat supplements in the rumen. By adjusting the ratios of EPA and DHA within the fat supplement, it is feasible to generate milk that caters to diverse consumer preferences and meet the standards of a source of omega-3 fatty acids.…”
Section: Rumen Fluid Polyunsaturated Fatty Acids (Pufa) Concentrationmentioning
confidence: 94%
“…The findings of this investigation suggest that supplementation of UFA and/or PUFA sources can improve fatty acid profile and reduce the negative effects of biohydrogenation in the rumen. Another study conducted by Gulati et al [30] also found that a transfer of 19-20% of EPA and DHA into milk is achievable from feed management, whether they are raised on pasture or fed with a diet high in inert fat supplements in the rumen. By adjusting the ratios of EPA and DHA within the fat supplement, it is feasible to generate milk that caters to diverse consumer preferences and meet the standards of a source of omega-3 fatty acids.…”
Section: Rumen Fluid Polyunsaturated Fatty Acids (Pufa) Concentrationmentioning
confidence: 94%